Peningkatan Manajemen Informasi Organisasi dengan Memanfaatkan Website - Subektiningsih Subektiningsih (Muria Jurnal Layanan Masyarakat, 2020)
Girirupo Youth Generation is a social organization that has the aim to advance the village of Girirupo in particular and all levels of society in general. The organization has internal and external activities. Internal activities involve active members of the organization, while external activities involve non-governmental organizations. In business processes these organizations have a lot of data that is processed into information. The management of this information is carried out by recording regularly using books. The information generated is passed on to members and the community through word of mouth, instant messaging services, as well as WhatsApp groups owned by the organization. Management and delivery of information has not been done in a structured. The ability of organizations to manage data and information becomes more effective and structured after training in information management. The ease and speed in delivering information can also be realized by having an organization's website, namely girirupomuda.com.